The Ottoman Archive Contains Records Pertaining to the Patronage of the Seljuk Sultan Ala Al-Din Kayqubad - Ayşegül Bekmez Yelen (Art-Sanat)
During his reign and beyond, the Seljuk Sultan Ala al-Din Kayqubad was renowned for his power and construction activities. His legacy as the most illustrious ruler of the Seljuk State is evident in records from the Ottoman Period. Kayqubad’s image endured for centuries after his death. The palaces constructed in Konya, Kayseri reflect the Sultan’s passion for architecture and art. The sudden and tragic death of the sultan marked the beginning of a period of decline for the Seljuk Empire. This study focuses on the buildings constructed by Kayqubad, as documented in Ottoman records centuries later. It is noteworthy that the buildings believed to have been built during the Seljuk period are referred to as Ala alDin in the Ottoman documents and among the people. The naming of some buildings after the sultan, despite explicitly mentioning the owner in their inscriptions, requires further examination. Additionally, historical documents reveal that some buildings, not mentioned in period sources and no longer extant, were constructed during Kayqubad’s. The research reveals structures built in the Seljuk Period but did not survive or were not previously known, providing an opportunity to evaluate the perception of Kayqubad and Seljuk art in the Ottoman Period.